Production cost and profitability of fingerlings production of tambaqui Colossoma macropomum in northeast of pará state, amazon, Brazil - Castro, Denys Roberto Corrêa; Campelo, Daniel Abreu Vasconcelos; Veras, Galileu Crovatto; Nunes, Zélia Maria Pimentel; Brabo, Marcos Ferreira; da Rocha, Rossineide Martins [UNESP] (My University, 2019)
Tambaqui Colossoma macropomum is the most important species for fish farming in the Pará State, since it adapts to different production systems, presents a regular supply of young forms throughout the year and has an attractive consumer market in the regional and national context. However, the fingerlings production of the species still can not meet the local demand, which leads producers to purchase this input in other units of the Federation, such as Tocantins, Rondônia and Mato Grosso. The objective of this study was to analyze the production cost and the profitability of the fingerlings production of tambaqui in the Northeast of Pará State. The methodology of operational cost and economic efficiency indicators was used to evaluate a project of 0.3 hectare of flooded area, distributed in three ponds of 1,000 m2. For the analysis of risk, we considered a variation in the number of reproductions made annually. The implantation cost of the project was estimated at R$ 286,857.06, with an effective operating cost of R$ 76,260.70, R$ 94,420.39 and R$ 112,580.09 and total operating cost of R$ 97,857.90, R$ 116,017.59 and R$ 134,177.29 for three, four and five reproductions per year, respectively. The gross revenue amounts were R$ 112,500.00, R$ 150,000.00 and R$ 187,500.00, operating income per month of R$ 1,220.18, R$ 2,831.87 and R$ 4,443.56, internal rate of return of 7%, 16% and 24%, and capital return period of 11.3, 5.4 and 3.8 years for the three scenarios analyzed, respectively. It was concluded that the fingerlings production of tambaqui presented attractive profitability from the realization of five reproductions per year, which represented approximately 1,250 thousand.
Keywords: Economic indicators; Fish farming; Induced reproduction